Chaos in a Single Op-Amp–Based Jerk Circuit: Experiments and Simulations - Tchitnga, Robert; Nguazon, Tekou; Louodop Fotso, Patrick H.; Gallas, Jason (IEEE Transactions on Circuits and Systems II: Express Briefs, 2016)
We report a five-component autonomous chaotic oscillator of jerky type, hitherto the simplest of its kind, using only one operational amplifier. The key component of the circuit is a junction field-effect transistor operating in its triode region, which provides a nonlinear resistor of antisymmetrical current–voltage characteristic, emulating a Colpitts-like chaotic circuit. We describe the experimental results illustrating the dynamical behavior of the circuit. In addition, we report numerical simulations of a model of the circuit which display good agreement with our measurements.
Keywords: Bifurcations; jerk oscillator; junction field-effect transistor (JFET); piecewise (PW) nonlinearity (NLT); simplest chaotic circuit I